Repeated seizures induce long-term increase in hippocampal benzodiazepine receptors. - McNamara, J O (1980)
Repeated seizures, whether induced by kindling or electroshock, caused a long-lasting (at least 24 hr) increase of [3H]diazepam binding in hippocampal membranes of Sprague-Dawley rats. Scatchard analyses demonstrated that increased numbers of binding sites accounted for the increase. Neither repeated hypoxia nor repeated administration of electrical current without inducing seizures caused an increase of [3H]diazepam binding. Regardless of the method used for seizure induction, the response was graded in that large numbers of seizures were required to induce significant increases, whereas fewer seizures induced only slight increases. We suggest that the receptor increases imply a heightened response to benzodiazepines and more powerful hippocampal recurrent inhibition.